Comprehensive Analysis of the Immune Infiltrates and PD-L1 of m6A RNA Methylation Regulators in Hepatocellular Carcinoma - Xu, Yangtao; He, Xiaoqin; Deng, Junjian; Xiong, Lin; Li, Yue; Zhang, Xiaoyu; Chen, Wenliang; Liu, Xin; Xu, Ximing (Frontiers in Cell and Developmental Biology, 2021)
Recently, N6-methyladenosine (m6A) RNA methylation in eukaryotic mRNA has become increasingly obvious in the pathogenesis and prognosis of cancer. Moreover, tumor microenvironment is involved in the regulation of tumorigenesis. In our research, the clinical data, including 374 tumor and 50 normal patients, were obtained from The Cancer Genome Atlas (TCGA). Then 19 m6A regulators were selected from other studies. Hepatocellular carcinoma (HCC) patients were clustered in cluster1/2, according to the consensus clustering for the m6A RNA regulators. We found that m6A regulators were upregulated in cluster1. The cluster1 was associated with higher programmed death ligand 1 (PD-L1) expression level, higher immunoscore, worse prognosis, and distinct immune cell infiltration compared with cluster2. Five risk signatures were identified, including YTH N6-methyladenosine RNA-binding protein 1, YTHDF2, heterogeneous nuclear ribonucleoprotein C, WT1-associated protein, and methyltransferase-like 3, based on univariate Cox and least absolute shrinkage and selection operator regression analysis. High-risk group and low-risk group HCC patients were selected based on the risk score. Similarly, the high-risk group was extremely associated with higher PD-L1 expression level, higher grade, and worse overall survival (OS). Also, cluster1 was mainly enriched in high-risk group. Receiver operating characteristic (ROC) and a nomogram were used to predict the ability and the probability of 3- and 5-year OS of HCC patients. The time-dependent ROC curve (AUC) reached 0.77, 0.67, and 0.68 at 1, 3, and 5 years in the training dataset. Also, AUC areas of 1, 3, and 5 years were 0.7, 0.63, and 0.55 in the validation dataset. The gene set enrichment analysis showed that MTOR signaling pathway and WNT signaling pathway were correlated with cluster1 and high-risk group. Collectively, the research showed that the m6A regulators were significantly associated with tumor immune microenvironment in HCC. Risk characteristics based on m6A regulators may predict prognosis in patients with HCC and provide a new therapeutic target for improving the efficacy of immunotherapy.